(NsOWREMENNYE PROCESSY W RUSSKIH NARODNYH GOWORAH (B:s [(NsBORNIK STATEJ(B] /s - (NbARANNIKOWA(B, (Nl(B.(Ni(B.s ((NsARATOW (B:s (NiZD(B-(NWO sARATOWSKOGO UN(B-(NTA(B,s, 1991)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE ST(B.s
Keywords: (NrUSSKIJ QZYKs -- (NdIALEKTYs